2022
DOI: 10.3390/ijerph19137938
|View full text |Cite
|
Sign up to set email alerts
|

Child Labor and Psychosocial Wellbeing: Findings from Ethiopia

Abstract: For children who work, there has been little research into the intricate relationship between their home lives and their work lives and the implications that this relationship might hold for their psychosocial development and functioning. This cross-sectional study was conducted in the Amhara region, Ethiopia, between March and April 2020 on a sample of 1311 working children with the aim, in part, of exploring ways in which various dimensions of children’s psychological wellbeing are influenced by their workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
1
0
0
Order By: Relevance
“…These findings on the effects of child labour are not surprising and reflect the large body of literature on the harmful effects of child labour, including studies in Brazil [19], Ethiopia [20] and India [21], where there are reported associations between hazardous/child labour and poor psychosocial well-being. The current study adds to the evidence base by demonstrating that children working under hazardous work conditions with/without child labour have greater psychosocial functioning difficulty.…”
Section: Discussionsupporting
confidence: 61%
“…These findings on the effects of child labour are not surprising and reflect the large body of literature on the harmful effects of child labour, including studies in Brazil [19], Ethiopia [20] and India [21], where there are reported associations between hazardous/child labour and poor psychosocial well-being. The current study adds to the evidence base by demonstrating that children working under hazardous work conditions with/without child labour have greater psychosocial functioning difficulty.…”
Section: Discussionsupporting
confidence: 61%
“…Work that keeps children away from home or peers, and forces them out of school can isolate these children and deprive them of social and educational opportunities. Work can also create conditions in which the child is exposed to risks, accidents, abuse and violence [ 9 ]. Child labor can have physical consequences such as bone fracture that manifests itself immediately, or have long-term affect like exposure to toxins that appears over time.…”
Section: Introductionmentioning
confidence: 99%